1999
DOI: 10.4141/a98-088
|View full text |Cite
|
Sign up to set email alerts
|

Apparent transfer efficiency of docosahexaenoic acid from diet to milk in dairy cows

Abstract: . W. 1999. Apparent transfer efficiency of docosahexaenoic acid from diet to milk in dairy cows. Can. J. Anim. 79: 565-568. Apparent transfer efficiency of docosahexaenoic acid from diet to milk in dairy cattle was investigated. Three levels of a fish meal-containing supplement, 4.5, 14.9, and 29.1% of dry matter intake were added to a basal diet. A linear decline (from 34% to 11%) in apparent transfer efficiency was observed, as level of supplement increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…The more prominent of the PUFA present in milkfats are: 20:3n-6, 20:4n-6 (arachidonic acid), 20:5n-3 (EPA), 22:4n-6, and 22:5n-3. DHA (22:6n-3) is present only in trace amounts in milkfat unless the cow's diet contained some fish or algal products (50,61,62); Figure 12B represents a milk from cows fed a fish meal diet, and Figure 13B a milk from cows fed a control diet.…”
Section: Figmentioning
confidence: 99%
“…The more prominent of the PUFA present in milkfats are: 20:3n-6, 20:4n-6 (arachidonic acid), 20:5n-3 (EPA), 22:4n-6, and 22:5n-3. DHA (22:6n-3) is present only in trace amounts in milkfat unless the cow's diet contained some fish or algal products (50,61,62); Figure 12B represents a milk from cows fed a fish meal diet, and Figure 13B a milk from cows fed a control diet.…”
Section: Figmentioning
confidence: 99%
“…Offer et al (1999) reported transfer coefficients of less than 0.03 for PUFA of chain length ≥ C 20 . Cant et al (1997) reported transfer efficiencies of 0.09 and 0.16 for EPA and DHA, respectively, whereas Wright et al (1999) reported that the transfer of EPA and DHA declined from 0.27 to 0.07, and 0.34 to 0.11, respectively, as intakes increased from 1.6 to 16 g/d. Palmquist and Griinari (2006) reported that only 10 mg of DHA/g of intake, 57 mg of EPA/g of intake, and 110 mg of DPA/ g of intake appeared in milk compared with the 17, 34, and 214 mg/g of DHA, EPA, and DPA intake, respectively, in the drinking water of the cows in the current study.…”
mentioning
confidence: 99%
“…Serum fatty acid analysis was conducted according to the methods of Wright et al [1999]. Briefly, serum fatty acid composition was quantified after lipid extraction (two extractions with 1:2 chloroform:methanol vol/vol) and transmethylated in the presence of boron trichloride and gas-liquid chromatography (Lipid Analytic, Guelph, ON).…”
Section: Serum Fatty Acid Analysismentioning
confidence: 99%